Negative electrode applied to lithium-hydrogen battery, preparation method of negative electrode and lithium-hydrogen battery
By forming a silicon nanomaterial coating on the metal foil current collector of the lithium-hydrogen battery and forming a lithium-philic interface, the problem of high cost and safety risks of the existing lithium-hydrogen battery negative electrode materials is solved, and a lithium-hydrogen battery with high energy density and high safety is achieved.
Patent Information
- Application Number
- CN202411987519.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing lithium-hydrogen batteries require the use of highly active lithium metal as the negative electrode when assembling, resulting in high production costs, difficult process and safety risks. At the same time, the energy density of single cells is low.
By forming a silicon nanomaterial coating on the metal foil current collector and forming a lithium-philic interface during the first charging process, it acts as the negative electrode precursor of the lithium-hydrogen battery and assembles in combination with an electrolyte containing lithium ions to achieve the embeddedness and stable deposition of lithium ions.
The production cost and process difficulty are reduced, the energy density of lithium-hydrogen batteries is improved, and the safety is improved because the high-reactive lithium metal is not directly used, and the Coulomb efficiency of lithium-hydrogen batteries can be maintained at more than 98.5%.
Smart Images

Figure CN119695053A_ABST
Abstract
Description
Technical Field
[0001] At least one embodiment of the present invention relates to a lithium-hydrogen battery, and more particularly to a negative electrode used in a lithium-hydrogen battery and a preparation method thereof, and a lithium-hydrogen battery. Background Art
[0002] With the continuous growth of global energy demand, the development and storage technology of clean energy has become the focus of research. At present, energy storage technology covers a variety of means, mainly including mechanical energy storage, electrochemical energy storage, electromagnetic energy storage and chemical energy storage. In the field of electrochemical energy storage, hydrogen batteries with catalytic hydrogen electrodes as negative electrodes have the advantages of low cost and long cycle life.
[0003] Taking nickel-hydrogen batteries as an example, they store and release energy through the hydrogen evolution reaction (HER) / hydrogen oxidation reaction (HOR) between charging and discharging. However, with hydrogen as the negative electrode, there are fewer choices of positive electrode materials and the operating voltage of the battery is low, and thus the energy density of the single cell is low. Therefore, by further expanding the working voltage of hydrogen batteries and giving full play to the advantages of hydrogen electrodes, lithium-hydrogen batteries will be a new battery system with broad application prospects. General lithium-hydrogen batteries require the use of more active lithium metal as the negative electrode during assembly, which has high production costs, difficult processes, and certain safety risks. Summary of the invention
[0004] In view of this, in order to at least partially solve the above-mentioned technical problems, the present invention provides a negative electrode for a lithium-hydrogen battery and a preparation method thereof, and a lithium-hydrogen battery, so as to reduce production costs and process difficulties and have improved energy density.
[0005] According to an embodiment of one aspect of the present invention, there is provided a method for preparing a negative electrode for a lithium-hydrogen battery, comprising:
[0006] Prepare silicon nanomaterial slurry; evenly scrape the silicon nanomaterial slurry onto one surface of a metal foil current collector, dry and roll to form a silicon nanomaterial coating on the metal foil current collector to form a negative electrode precursor; and assemble the negative electrode precursor and a lithium ion-containing electrolyte into a lithium-hydrogen battery for the first charge, so that lithium ions are embedded in the negative electrode precursor to form a lithium-philic interface to form a negative electrode.
[0007] According to another embodiment of the present invention, there is provided a negative electrode for a lithium-hydrogen battery obtained by the above-mentioned preparation method, comprising:
[0008] Metal foil current collector;
[0009] as well as
[0010] The lithiophilic interface, including a lithium-silicon alloy, is located on the metal foil current collector.
[0011] According to an embodiment of one aspect of the present invention, there is provided a lithium-hydrogen battery, comprising: an electrolyte; a positive electrode, adapted to conduct proton (H + ) and gaseous H2; the negative electrode prepared as above is suitable for the redox reaction between lithium metal and lithium ions at the interface between the negative electrode and the electrolyte.
[0012] According to the method for preparing the negative electrode for lithium-hydrogen battery provided by the above embodiment of the present invention, a silicon nanomaterial coating is formed on the metal foil current collector, and a lithium-philic interface is formed in situ on the silicon nanomaterial coating during the first charging process. The lithium-philic interface is conducive to efficient, dense and stable subsequent lithium deposition, and the negative electrode is obtained. The negative electrode is applied to lithium-hydrogen battery to obtain a lithium-hydrogen battery with high energy density. In addition, the negative electrode provided by the present invention is based on the existing material system, has low preparation cost, and is safer than pure lithium negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings of the embodiments will be briefly introduced below. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0014] Figure 1 A schematic flow chart of a method for preparing a negative electrode for a lithium-hydrogen battery provided in an embodiment of the present invention;
[0015] Figure 2 A schematic diagram of a negative electrode applied to a lithium-hydrogen battery provided by an embodiment of the present invention;
[0016] Figure 3 A schematic diagram of a lithium-hydrogen battery provided by an embodiment of the present invention;
[0017] Figure 4 A scanning electron microscope image of silicon nanoparticles used in preparing the negative electrode provided in Example 1 of the present invention;
[0018] Figure 5 A schematic diagram of a metal foil current collector loaded with a silicon nanomaterial coating provided in Example 1 of the present invention;
[0019] Figure 6 The charge and discharge curve of the lithium-hydrogen battery provided in Example 1 of the present invention under a current density of 1000 mA / g and a specified capacity test of 1000 mAh / g, wherein mA / g represents the current passing through the positive electrode catalyst (Pt / C) per unit mass, and mAh / g represents the electrical energy catalyzed by the positive electrode catalyst (Pt / C) for the conversion of hydrogen / protons;
[0020] Figure 7 A comparison chart of the cycle performance of the lithium-hydrogen battery provided in Example 1 of the present invention and the cycle performance of the lithium-hydrogen battery of Comparative Example 1;
[0021] Figure 8 The charge and discharge curve of the lithium-hydrogen battery provided in Example 2 of the present invention under the current density of 1000 mA / g and the specified capacity test of 1000 mAh / g; and
[0022] Fig. 9 The charge and discharge curve of the lithium-hydrogen battery provided in Example 3 of the present invention under a current density of 1000 mA / g and a specified capacity test of 1000 mAh / g;
[0023] Description of reference numerals:
[0024] 1- negative electrode;
[0025] 11-metal foil current collector;
[0026] 12-Silicon nanomaterial coating;
[0027] 13-lithiophilic interface;
[0028] 2-Organic electrolyte;
[0029] 3-Solid electrolyte membrane;
[0030] 4- cathode electrolyte;
[0031] 5- Positive electrode. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. However, the present invention can be implemented in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, providing these embodiments will make the invention thorough and complete and fully convey the scope of the present invention to those skilled in the art. In the accompanying drawings, for clarity, the sizes and relative sizes of layers and regions may be exaggerated, and the same reference numerals throughout represent the same elements.
[0033] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0034] Figure 1 A schematic flow chart of a method for preparing a negative electrode for a lithium-hydrogen battery provided in an embodiment of the present invention.
[0035] According to an exemplary embodiment of the present invention, the present invention provides a method for preparing a negative electrode for a lithium-hydrogen battery, referring to Figure 1 As shown, it includes: operation S01 to operation S03.
[0036] Operation S01: preparing silicon nanomaterial slurry.
[0037] In some embodiments, preparing silicon nanomaterial slurry includes: mixing silicon nanoparticles, a binder, and a conductive agent to obtain a mixed solid material, dropping a solvent into the mixed solid material, stirring at room temperature for 2 hours to 8 hours, and then vacuum degassing to obtain silicon nanomaterial slurry.
[0038] In some embodiments, the silicon nanoparticles have the general formula SiO x , where 0<x<2; the particle size D50 of the silicon nanoparticles is any value in the range of 50nm~500nm, for example, 50nm, 100nm, 200nm, 300nm, 500nm, but not limited to the values cited. Nano-scale silicon materials have the smallest expansion effect and are the most stable as silicon materials. The particle size D50 of the silicon nanoparticles is 50nm~500nm, which can ensure the high stability of the in-situ formed Li-SiOx alloy and avoid the destruction of the structure due to the expansion effect of Si.
[0039] In some embodiments, the binder includes one or more of carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), sodium alginate (Alg), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), polyamide (PAI), polyvinyl alcohol (PEI), and polyimide (PI).
[0040] In some embodiments, the conductive agent includes one or more of acetylene black, Ketjen black, carbon nanotubes, and graphene.
[0041] In some embodiments, the solvent used is one or more of deionized water, ethylene glycol dimethyl ether (DMF), N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DME).
[0042] In some embodiments, the solid-liquid ratio of the mixed solid material to the solvent is any value in the range of 0.05 kg / L to 0.2 kg / L, for example, 0.05 kg / L, 0.1 kg / L, 0.15 kg / L, 0.18 kg / L, 0.2 kg / L, but is not limited to the values cited. The viscosity of the coating slurry formed by the solid-liquid ratio of the mixed solid material to the solvent being 0.05 kg / L to 0.2 kg / L can ensure uniform coating.
[0043] In some embodiments, the mass ratio of silicon nanoparticles to adhesive is (1~8):1, for example, 1:1, 2:1, 4:1, 6:1, 8:1, but not limited to the values cited. Different Si material particle sizes need to match different adhesive contents, because the smaller the particle size, the larger the specific surface area of the silicon material, and more adhesive is needed to ensure the coating effect. According to experiments, for silicon nanoparticles with a particle size D50 of 50nm~500nm, a good coating effect can be achieved when the mass ratio of silicon nanoparticles to adhesive is (1~8):1. In some embodiments, the ratio of the mass of the conductive agent to the mass of the adhesive is 0~50%, and is not 0.
[0044] In some embodiments, the silicon nanoparticles include one or more of silicon, silicon dioxide, and silicon oxides.
[0045] In operation S02, the silicon nanomaterial slurry is evenly scraped onto a surface of the metal foil current collector, and after drying and rolling, a silicon nanomaterial coating is formed on the metal foil current collector to form a negative electrode precursor.
[0046] In some embodiments, the metal foil current collector is a metal and its alloys, and the metal foil current collector includes one or more of Cu, Ag, Au, Ti, Al, Ni, In, Sr and Ba.
[0047] It should be noted that the thickness of the metal foil current collector is not limited here and can be set according to actual needs.
[0048] In operation S03, the negative electrode precursor and the electrolyte containing lithium ions are assembled into a lithium-hydrogen battery for the first charge, so that the lithium ions are embedded in the negative electrode precursor to form a lithium-philic interface to form a negative electrode.
[0049] According to an embodiment of the present invention, during the first charging process of the assembled lithium-hydrogen battery, lithium ions in the electrolyte of the lithium-hydrogen battery are embedded in the silicon nanomaterial coating to form a lithium-silicon alloy (lithophilic interface), and the lithium-philic interface will exist permanently after formation.
[0050] Figure 2 A schematic diagram of a negative electrode applied to a lithium-hydrogen battery provided in an embodiment of the present invention.
[0051] According to an exemplary embodiment of the present invention, the present invention provides a negative electrode for a lithium-hydrogen battery, referring to Figure 2 As shown, including:
[0052] Metal foil current collector 11;
[0053] The lithium-philic interface 13 comprises a lithium-silicon alloy. The lithium-philic interface is formed when the lithium-hydrogen battery is charged for the first time. The lithium-philic interface 13 is located on the metal foil current collector 11 .
[0054] In some embodiments, the thickness of the silicon nanomaterial coating formed on the metal foil current collector 11 is any value between 1 μm and 5 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, but is not limited to the above values.
[0055] In some embodiments, the sum of the thicknesses of the lithium-philic interface 13 formed in situ by the 1 μm to 5 μm silicon nanomaterial coating is 5 μm to 10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, but not limited to the values cited. If the thickness of the silicon nanomaterial coating is too small, the Li-SiOx lithium-philic layer that can be formed is too thin, and the effect of stabilizing the negative electrode (keeping the negative electrode stable in the cycle) is not obvious. If the thickness is too large, the stress is too large, and it is easy to peel off during the charge and discharge cycle.
[0056] Figure 3 A schematic diagram of a lithium-hydrogen battery provided in an embodiment of the present invention.
[0057] According to an exemplary embodiment of the present invention, the present invention provides a lithium-hydrogen battery, referring to Figure 3 As shown, it includes a negative electrode 1, an organic electrolyte 2, a solid electrolyte membrane 3, a positive electrode electrolyte 4, and a positive electrode 5 in sequence.
[0058] According to an embodiment of the present invention, the positive electrode of the lithium-hydrogen battery generates gaseous H2 and protons (H + ) during the redox reaction at the cathode, and a redox reaction between lithium metal and lithium ions occurs at the anode. Specifically, during charging, hydrogen is oxidized into protons (H + ), lithium ions in the electrolyte (Li + ) is reduced to lithium metal and deposited on the negative electrode. During discharge, the protons of the positive electrode in the battery cavity are reduced to H2, and the lithium metal at the negative electrode is oxidized to lithium ions. This process is reversible, allowing the battery to be charged and discharged for multiple cycles without failure.
[0059] According to an embodiment of the present invention, the active material (lithium metal) of the negative electrode provided by the present invention is formed during charging and disappears during discharging, so that there is no inactive mass in the negative electrode. In other words, the lithium active material provided by the present invention can be 100% converted into lithium metal and deposited on the negative electrode precursor to form a negative electrode. Compared with directly using lithium metal as the negative electrode, it can achieve extremely high active material utilization and extremely high energy density of lithium-hydrogen batteries.
[0060] According to an embodiment of the present invention, a negative electrode for lithium-hydrogen electrode and a preparation method thereof are provided, which no longer directly uses highly reactive lithium as the negative electrode, but uses a copper foil current collector loaded with a silicon nanomaterial coating as a negative electrode precursor. Under this design, the manufacture of lithium-hydrogen batteries will become simple, safe and low-cost. The lithium of the lithium-hydrogen battery will be deposited on the silicon nanomaterial coating during the first cycle of charging to form a lithium-philic interface of the lithium-silicon alloy, and subsequent lithium ions will be deposited on the lithium-philic interface. This design greatly improves the energy density of the lithium-hydrogen battery because there is no pre-use of a lithium negative electrode.
[0061] According to an embodiment of the present invention, the negative electrode-assembled lithium-hydrogen battery of the present invention can achieve an ultra-high reversible surface capacity, which is specifically manifested in that the coulombic efficiency (discharge capacity / charge capacity) of the negative electrode-assembled lithium-hydrogen battery of the present invention can be maintained above 98.5%.
[0062] It should be noted that the silicon negative electrode (using silicon as the negative electrode) in the related technology will expand three times in volume during the charge and discharge process, accelerating the damage of the negative electrode; compared with the silicon negative electrode, the negative electrode provided in the embodiment of the present invention remains stable after forming a lithium-philic interface, and its volume is not easy to expand, which is conducive to maintaining the stable performance of the negative electrode.
[0063] The following schematically illustrates the designed negative electrode for lithium-hydrogen battery and its preparation method, and the lithium-hydrogen battery. It should be noted that the example is only a specific embodiment of the present invention and cannot limit the protection scope of the present invention.
[0064] Example 1
[0065] Preparation of copper foil current collector loaded with silicon nanomaterial coating.
[0066] Specifically, in an air environment at normal temperature and pressure, Si nanoparticles and CMC powder were mixed in a ratio of 300 mg and 100 mg, 50 mg of conductive carbon black was added, and then stirred for 2 hours to mix the solid powders evenly. Then 5 mL of deionized water was slowly added to the stirring mixed powder. After the addition was completed, the slurry continued to stir for 6 hours. The slurry after homogenization was placed in a vacuum chamber to remove bubbles for 10 seconds, and then an appropriate amount of slurry was dripped on the cleaned copper foil surface, and the slurry was evenly coated with a scraper, and the scraper thickness was set to 2 μm. The coated copper foil current collector was placed in an oxygen-proof oven and dried at 75°C for 6 hours to obtain a negative electrode precursor.
[0067] Figure 4 This is a scanning electron microscope image of the silicon nanoparticles used to prepare the negative electrode provided in Example 1 of the present invention.
[0068] refer to Figure 4 As shown, the particle size of the silicon nanoparticles is approximately 1000 nm.
[0069] Figure 5 Schematic diagram of a metal foil current collector loaded with a silicon nanomaterial coating provided in Example 1 of the present invention.
[0070] refer to Figure 5 As shown, a silicon nanomaterial coating 12 is formed on the copper foil current collector 11 .
[0071] Prepare a lithium-hydrogen battery. Specifically, a lithium salt is dissolved in a mixed organic solvent (the volume ratio of DME to DOL is 1:1) to form an organic electrolyte 2. Lithium aluminum titanium phosphate (LATP) is used as a solid electrolyte separator 3. Sulfuric acid is used as a positive electrode electrolyte 4. A 5% mass fraction Pt / C catalyst is selected as a positive electrode catalyst, PVDF is used as a binder, NMP is used as a solvent, and the slurry is applied on a gas diffusion layer (GDL) to prepare a positive electrode 5.
[0072] The negative electrode precursor prepared in Example 1, the organic electrolyte 2, the solid electrolyte separator 3, the positive electrode electrolyte 4, and the positive electrode 5 are assembled into a lithium-hydrogen battery.
[0073] refer to Figure 1 As shown, after the assembled lithium-hydrogen battery is charged for the first time, a lithium-philic interface 13 is formed in situ on the silicon nanomaterial coating 12 of the negative electrode precursor.
[0074] Figure 6 The charge and discharge curves of the lithium-hydrogen battery provided in Example 1 of the present invention under a current density of 1000 mA / g and a specified capacity test of 1000 mAh / g.
[0075] refer to Figure 6 As shown, the lithium-hydrogen battery prepared in Example 1 was tested using a charge and discharge current of 1000 mA / g and a specified capacity of 1000 mAh / g. The curved curve portion at the initial stage of the first cycle of charging is the process of forming a lithium-philic interface. After the lithium-philic interface is formed in the first cycle of charging, the curved curve disappears during the second cycle of charging.
[0076] The total weight of the electrode sheet nano-coating in Example 1 is 0.12 mg. According to the mass ratio, the Si material content can be calculated to be 0.09 mg. The theoretical capacity of the Si material is 4200 mAh / g. The capacity required for charging the lithium-silicon alloy can be calculated to be: 0.09 / 1000*4200=0.378 mAh.
[0077] The lithium-hydrogen battery cathode catalyst content is 1 mg, and the calculated capacity is 378 mAh / g. Figure 6 The slope of the charging curve in the first lap is consistent with the flat position.
[0078] Comparative Example 1
[0079] The process of preparing the lithium-hydrogen battery is the same as that of Example 1, except that the negative electrode uses a copper current collector.
[0080] Figure 7 This is a comparison chart of the cycle performance of the lithium-hydrogen battery provided in Example 1 of the present invention and the cycle performance of the lithium-hydrogen battery of Comparative Example 1.
[0081] refer to Figure 7 As shown, the electrochemical performance of the lithium-hydrogen battery of Example 1 of the present invention is significantly better than that of the lithium-hydrogen battery of Comparative Example 1. In addition, the battery of Example 1 of the present invention also has good cycle stability. Compared with the lithium-hydrogen battery of Comparative Example 1, the lithium-hydrogen battery of Example 1 has a higher utilization rate of lithium metal during the cycle, and its reaction has a higher coulombic efficiency during the cycle (the coulombic efficiency of the lithium-hydrogen battery of Example 1 of the present invention reaches 98.5%, and the coulombic efficiency of the lithium-hydrogen battery of Comparative Example 1 is less than 98%). At the same time, Example 1 has a more stable cycle than Comparative Example 1, which is manifested in Figure 7 Embodiment 1 of the present invention has a smoother coulombic efficiency curve and increases steadily during the cycle process.
[0082] This is because in Comparative Example 1, the lithium metal layer is directly deposited on the copper current collector, which will cause the deposited lithium metal structure to be loose, with many defects, and lithium dendrites are prone to appear. The lithium-hydrogen battery formed as the negative electrode is prone to performance degradation during the cyclic charge and discharge process. The negative electrode of Example 1 of the present invention first deposits a silicon nanomaterial coating on the metal foil current collector, and forms a lithium-philic interface in situ on the silicon nanomaterial coating. The lithium-philic interface induces the lithium metal layer to form a dense, uniform and thicker metal alloy as the negative electrode. The negative electrode has a larger capacity and can remain stable during the cyclic charge and discharge process.
[0083] Example 2
[0084] The process of preparing the lithium-hydrogen battery is the same as that of Example 1, except that the silicon nanoparticles used to prepare the negative electrode precursor include SiO2.
[0085] Prepare a copper foil current collector loaded with silicon nanomaterial coating. Specifically, under normal temperature and pressure air environment, SiO2 nanoparticles and PVDF powder are mixed in a ratio of 400 mg and 100 mg, 50 mg of conductive carbon black is added, and then stirred for 2 hours to mix the solid powder evenly. Then 10 mL of NMP is slowly added to the stirring mixed powder. After the addition is completed, the slurry continues to stir for 8 hours. Take the slurry after homogenization and place it in a vacuum chamber to defoam for 10 seconds, then take an appropriate amount of slurry and drop it on the cleaned copper foil surface, and use a doctor coater to evenly coat the slurry, and the doctor blade thickness is set to 4 μm. The coated copper foil current collector is placed in an oxygen-proof oven at 80 ° C for 6 hours to obtain a negative electrode precursor.
[0086] Figure 8 The charge and discharge curves of the lithium-hydrogen battery provided in Example 2 of the present invention under a current density of 1000 mA / g and a specified capacity test of 1000 mAh / g.
[0087] refer to Figure 8 As shown in the figure, at the beginning of charging, the voltage curve gradually rises with a certain curvature, which represents the process of SiOx and Li alloying, that is, the formation process of the lithium-philic interface. After the silicon nanomaterial coating is completely embedded with lithium, the voltage curve begins to flatten, which is a manifestation of the stable deposition of lithium metal. In the subsequent discharge process, 2.5V is set as the voltage cutoff, which avoids the discharge of lithium-embedded SiOx.
[0088] Example 3
[0089] The process of preparing the lithium-hydrogen battery is the same as that of Example 1, except that the silicon nanoparticles used to prepare the negative electrode precursor include SiO.
[0090] Prepare a copper foil current collector loaded with silicon nanomaterial coating. Specifically, under normal temperature and pressure air environment, SiO nanoparticles and PAN powder were mixed in a ratio of 400 mg and 50 mg, 20 mg of conductive carbon black was added, and then stirred for 2 hours to mix the solid powders evenly. Then 6 mL of DMF was slowly added to the stirring mixed powder. After the addition was completed, the slurry continued to stir for 6 hours. The slurry after homogenization was placed in a vacuum chamber to defoam for 10 seconds, and then an appropriate amount of slurry was dripped on the cleaned copper foil surface, and the slurry was evenly coated with a doctor coater, and the doctor blade thickness was set to 3 μm. The coated copper foil current collector was placed in an oxygen-proof oven and dried at 80°C for 6 hours to obtain a negative electrode precursor.
[0091] Fig. 9 The charge and discharge curves of the lithium-hydrogen battery provided in Example 3 of the present invention under a current density of 1000 mA / g and a specified capacity test of 1000 mAh / g.
[0092] refer to Fig. 9 As shown in the figure, at the beginning of charging, the voltage curve gradually rises with a certain curvature, which represents the process of SiOx and Li alloying, that is, the formation process of the lithium-philic interface. After the silicon nanomaterial coating is completely embedded with lithium, the voltage curve begins to flatten, which is a manifestation of the stable deposition of lithium metal. In the subsequent discharge process, 2.5V is set as the voltage cutoff, which avoids the discharge of lithium-embedded SiOx.
[0093] Example 4
[0094] The process of preparing the lithium-hydrogen battery is the same as that in Example 3, except that the binder used to prepare the negative electrode precursor is CMC, and the mass ratio of SiO nanoparticles to CMC powder is 3:1.
[0095] Prepare a copper current collector negative electrode loaded with silicon nanomaterial coating. Specifically, under normal temperature and pressure air environment, SiO nanoparticles and CMC powder were mixed in a ratio of 300 mg and 100 mg, 10 mg of conductive carbon black was added, and then stirred for 2 hours to mix the solid powder evenly. Then 5 mL of deionized water was slowly added to the stirring mixed powder. After the addition was completed, the slurry continued to stir for 6 hours. The slurry after homogenization was placed in a vacuum chamber to defoam for 10 seconds, and then an appropriate amount of slurry was dripped on the cleaned copper foil surface, and the slurry was evenly coated with a doctor blade, and the doctor blade thickness was set to 1 μm. The coated copper foil current collector was placed in an oxygen-proof oven and dried at 80°C for 6 hours to obtain a negative electrode precursor.
[0096] Example 5
[0097] The process of preparing the lithium-hydrogen battery is the same as that of Example 4, except that the silicon nanoparticles used in preparing the negative electrode precursor include SiO 1.2 .
[0098] A copper current collector loaded with a silicon nanomaterial coating is prepared. Specifically, SiO 1.2 Nanoparticles and CMC powder were mixed in a ratio of 300 mg and 100 mg, and 10 mg of conductive carbon black was added. The solid powder was then stirred for 2 hours to mix evenly. Then 4.8 mL of deionized water was slowly added to the mixed powder. After the addition was completed, the slurry continued to stir for 6 hours. The homogenized slurry was placed in a vacuum chamber to remove bubbles for 10 seconds, and then an appropriate amount of slurry was dripped on the cleaned copper foil surface. The slurry was evenly coated with a scraper, and the scraper thickness was set to 2 μm. The coated copper foil current collector was placed in an oxygen-proof oven at 80 ° C for 6 hours to obtain a negative electrode precursor.
[0099] Example 6
[0100] The process of preparing the lithium-hydrogen battery is the same as that of Example 5, except that the silicon nanoparticles used in preparing the negative electrode precursor include SiO 0.8 .
[0101] A copper foil current collector loaded with a silicon nanomaterial coating is prepared. Specifically, SiO 0.8 Nanoparticles and CMC powder were mixed in a ratio of 300 mg and 100 mg, and 10 mg of conductive carbon black was added, followed by stirring for 2 hours to mix the solid powders evenly. Then 4.8 mL of deionized water was slowly added to the stirred mixed powder. After the addition was completed, the slurry continued to stir for 6 hours. The homogenized slurry was placed in a vacuum chamber to remove bubbles for 10 seconds, and then an appropriate amount of slurry was dripped on the cleaned copper foil surface, and the slurry was evenly coated with a scraper, and the scraper thickness was set to 2 μm. The coated copper foil current collector was placed in an oxygen-proof oven at 80°C for 6 hours to obtain a negative electrode precursor.
[0102] The ordinal numbers used in the specification and claims, such as "first", "second", "third", etc., to modify the corresponding elements, do not themselves mean that the elements have any ordinal numbers, nor do they represent the order of one element and another element, or the order in the manufacturing method. The use of these ordinal numbers is only used to clearly distinguish a component with a certain name from another component with the same name.
[0103] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode for a lithium-hydrogen battery, characterized in that: include: preparing silicon nanomaterial slurry; Evenly scraping the silicon nanomaterial slurry onto one surface of the metal foil current collector, drying and rolling to form a silicon nanomaterial coating on the metal foil current collector to form a negative electrode precursor; as well as The negative electrode precursor and the electrolyte containing lithium ions are assembled into a lithium-hydrogen battery for the first charge, so that the lithium ions are embedded in the negative electrode precursor to form a lithium-philic interface to form the negative electrode.
2. The preparation method according to claim 1, characterized in that: The preparation of the silicon nanomaterial slurry comprises: Silicon nanoparticles, a binder and a conductive agent are mixed to obtain a mixed solid material, a solvent is dripped into the mixed solid material, and after stirring at room temperature, vacuum degassing is performed to obtain the silicon nanomaterial slurry.
3. The preparation method according to claim 2, characterized in that: The solid-liquid ratio of the mixed solid material and the solvent is 0.05kg / L~0.2kg / L; The mass ratio of silicon nanoparticles to binder is 1 to 8; The ratio of the mass of the conductive agent to the mass of the adhesive is 0 to 50% and is not zero.
4. The preparation method according to claim 2, characterized in that: The silicon nanoparticles include one or more of silicon, silicon dioxide and silicon oxides.
5. The preparation method according to claim 1, characterized in that: The metal foil current collector is a metal or its alloy. The metal foil current collector includes one or more of Cu, Ag, Au, Ti, Al, Ni, In, Sr and Ba.
6. The preparation method according to claim 1, characterized in that: The thickness of the silicon nanomaterial coating (12) is 1 μm to 5 μm.
7. A negative electrode for lithium-hydrogen battery obtained by the preparation method according to any one of claims 1 to 6, characterized in that: include: Metal foil current collector (11); as well as A lithium-philic interface (13) comprising a lithium-silicon alloy is located on the metal foil current collector (11).
8. The negative electrode according to claim 7, characterized in that The lithium-philic interface is formed when the lithium-hydrogen battery is charged for the first time.
9. The negative electrode according to claim 7, characterized in that The thickness of the lithium-philic interface (13) is 5 μm to 10 μm.
10. A lithium-hydrogen battery, characterized in that: include: Electrolyte; A positive electrode adapted to perform a redox reaction between protons and gaseous H2 at an interface between the positive electrode and the electrolyte; The negative electrode according to any one of claims 7 to 9, suitable for performing a redox reaction between lithium metal and lithium ions at the interface between the negative electrode and the electrolyte.
Citation Information
Patent Citations
Silicon-containing lithium cathode, preparation method thereof and lithium sulfur battery with silicon-containing lithium cathode
CN102694158A
Three-dimensional composite current collector and preparation method thereof
CN112670516A
Metal-hydrogen battery and preparation method thereof
CN113328177A
Silicon / carbon-based modified lithium metal negative electrode current collector as well as preparation method and application thereof
CN115207361A
Negative current collector, negative-electrode-free lithium metal secondary battery and preparation method of negative current collector and negative-electrode-free lithium metal secondary battery
CN117317237A